Solidification/stabilization of fly ash contaminated with radiocesium into geopolymers - Šimon Rezbárik; Lenka Vavrincová; Martin Valica; Vanda Adamcová; Stanislav Sekely; Ján Rezbárik; Miroslav Horník (Przegląd Naukowy Inżynieria i Kształtowanie Środowiska)
The main goal of this work was to evaluate the possibilities of solidifying fly ashes contaminated with 137Cs into geopolymer waste forms. In the first step, physico-chemical characterization of fly ash originating from the thermal power plant in Vojany (Slovak Republic) was carried out. Before the preparation of the geopolymer waste forms (ternary mixture Geocem, GEOFIX, s.r.o., Slovak Republic) containing fly ash at percentage weight proportions of 5%, 10%, 20%, and 40%, the fly ash was artificially contaminated with a 137CsCl solution. The 137Cs activity was measured by scintillation gamma-spectrometry. The leachability test conducted according to the American National Standard ANSI/ANS-16.1-1986 over five days showed that the geopolymer waste forms with fly ash contents of 5%, 10% and 20% met the required leachability index limits with values more than 6. The compressive strength test also confirmed that the samples with 40% ash content did not meet the required 5 MPa limit for their disposal as a radioactive waste.